Trade and economic relations between the Caribbean Community (CARICOM) and the Central American Common Market (CACM) - Nicholls, Shelton...[et al.] ([Caribbean Centre for Monetary Studies] [St. Augustine]TT, 2001)
Assesses the feasibility of a potential Free Trade Agreement between CARICOM and the Central American Common Market against the background of the current trade policy environment in the Western Hemisphere and the uncertainity created by the recently aborted Seattle WTO Ministerial.